A TRANSITION OF THE DRINKING WATER PROVISION IN INDONESIA - Sugiyono, - (TAPAK [Teknologi Aplikasi Konstruksi] : Jurnal Program Studi Teknik Sipil, 2012)
The result of this process are four alternative strategies. Finally the most reasonable and appropriate strategy is discussed in the end of this part.